Efektivitas Model Pembelajaran Kooperatif Tipe Jigsaw Dengan Menggunakan Media Visual Terhadap Hasil Belajar PKn Pada Siswa Kelas VII SMP Al-Hasany Banyoneng Laok Geger Bangkalan - Aan Syafi’i; Hefi Rusnita Dewi; M. Sahid (Penerbit STKIP PGRI Bangkalan, 2019)
Research used in this research is quantitative descriptive research. Quantitative research is a research method based on the philosophy of positivism, used to examine specific populations or samples for which data collection uses quantitative data analysis. Based on the data analysis, it was concluded that showing citizenship education (PKn) learning using visual media, there were differences in student learning outcomes after using using visual media in class VIII subjects in Al-Hasany Banyoneng Banyaneng Laok Geger Bangkalan.